Cell components of tumor microenvironment in lung adenocarcinoma: Promising targets for small-molecule compounds - Mingyu Han; Feng Wan; Bin Xiao; Junrong Du; Cheng Peng; Fu Peng; Xiangxiang Pan (Chinese Medical Journal)
Abstract. Lung cancer is one of the most lethal tumors in the world with a 5-year overall survival rate of less than 20%, mainly including lung adenocarcinoma (LUAD). Tumor microenvironment (TME) has become a new research focus in the treatment of lung cancer. The TME is heterogeneous in composition and consists of cellular components, growth factors, proteases, and extracellular matrix. The various cellular components exert a different role in apoptosis, metastasis, or proliferation of lung cancer cells through different pathways, thus contributing to the treatment of adenocarcinoma and potentially facilitating novel therapeutic methods. This review summarizes the research progress on different cellular components with cell–cell interactions in the TME of LUAD, along with their corresponding drug candidates, suggesting that targeting cellular components in the TME of LUAD holds great promise for future theraputic development.